Current approaches on warming up for sports performance: A critical review - Gil, M. H.; Neiva, H. P.; Sousa, A. C.; Marques, M. C.; Marinho, D. A. (Strength and Conditioning Journal, 2019)
Warm-up procedures have become relevant for coaches, researchers, and sports professionals in recent years. Several studies have been conducted to verify the effects of different preactivities, regarding differing volume, intensity, rest, and specificity, and the warm-up is now widely accepted as an essential practice to improve performance. Research is now focusing on the effects of static and dynamic stretches, postactivation potentiation phenomenon, and optimization of waiting periods with passive warm-up approaches. In this brief review, we critically analyze the emerging methods and strategies of warm-up that have been investigated and used before competitive events.